Mycobacterium tuberculosis Cell Wall Fragments Released upon Bacterial Contact with the Human Lung Mucosa Alter the Neutrophil Response to Infection - Scordo, Julia M.; Arcos, Jesús; Kelley, Holden V.; Diangelo, Lauren; Sasindran, Smitha J.; Youngmin, Ellie; Wewers, Mark D.; Wang, Shu-Hua; Balada-Llasat, Joan-Miquel; Torrelles, Jordi B. (Frontiers in Immunology, 2017)
In 2016 the World Health Organization (WHO) reported that one person dies of tuberculosis every 21 seconds. A host environment that Mycobacterium tuberculosis (M.tb) finds during its route of infection is the lung mucosa bathing the alveolar space located in the deepest regions of the lungs. We published that human lung mucosa, or alveolar lining fluid (ALF), contains an array of hydrolytic enzymes that can significantly alter the M.tb surface during infection by cleaving off parts of its cell wall. This interaction results in two different outcomes: modifications on the M.tb cell wall surface and release of M.tb cell wall fragments into the environment. Typically, one of the first host immune cells at the site of M.tb infection is the neutrophil. Neutrophils can mount an extracellular and intracellular innate immune response to M.tb during infection. We hypothesized that exposure of neutrophils to ALF-induced M.tb released cell wall fragments would prime neutrophils to control M.tb infection better. Our results show that ALF-fragments activate neutrophils leading to an increased production of inflammatory cytokines and oxidative radicals. However, neutrophil exposure to these fragments reduces production of chemoattractants (i.e. Interleukin-8), and degranulation, with the subsequent reduction of myeloperoxidase release; and does not induce cytotoxicity. Unexpectedly, these ALF-fragments derived modulations in neutrophil activity do not further, either positively or negatively, contribute to the intracellular control of M.tb growth during infection. However, secreted products from neutrophils primed with ALF-fragments are capable of regulating the activity of resting macrophages. These results indicate that ALF-induced M.tb fragments could further contribute to the control of M.tb growth and local killing by resident neutrophils by switching on the total oxidative response and limiting migration of neutrophils to the infection site.